Fluoroquinolones in ambulatory surgical practice: whom, when, how? - A. V. Golub; V. G. Pleshkov; V. V. Privol'nev (Амбулаторная хирургия)
The articLe discusses the indications and conditions for the use of fLuoroquinoLones (ciprofloxacin, LevofLoxacin, moxifLoxacin) in surgicaL infections of the skin and soft tissues in ambuLatory patients. Various aspects of the use of fLuoroquinoLones are described from the standpoint of rationaL antibiotic therapy, the current sensitivity status of microbiaL agents in Russia, high-quaLity comparative cLinicaL findings and in accordance with the nationaL guideLines.he articLe discusses the indications and conditions for the use of fLuoroquinoLones (ciprofloxacin, LevofLoxacin, moxifLoxacin) in surgicaL infections of the skin and soft tissues in ambuLatory patients. Various aspects of the use of fLuoroquinoLones are described from the standpoint of rationaL antibiotic therapy, the current sensitivity status of microbiaL agents in Russia, high-quaLity comparative cLinicaL findings and in accordance with the nationaL guideLines.